Technological Complex for Processing of Solid Household and Treatment Facilities Waste with Biogas Obtaining - Seryogin, Oleksandr; Vasylenko, Oleksandr; Riedel, Frank J.; Aigner, Helmut (My University, 2021)
A concept has been developed for processing of biologically active sludge from municipal wastewater treatment plants in combination with the organic fraction of municipal solid waste using the BioTech Process. The complex, which makes it possible to implement the proposed concept, does not require additional land plots, and classified secondary raw materials, biogas and high-quality biofertilizers suitable for use in the agricultural industry are the products of its activity. The proposed concept will allow solving several problems at once due to the construction of a waste recycling plant on the territory of the filtration zone of the existing water treatment facilities. The new processing plant will be used not only for processing and sorting of solid waste, but also for treating sludge from wastewater treatment plants, together with organic waste obtained from solid waste in the BioTech Process to obtain biogas and biofertilizers, the so-called compost. The new recycling plant will be environmentally friendly and, among other benefits, will be able to process of municipal solid waste with preliminary sorting and separation of recyclable materials.
Keywords: biogas; recycling; sewage treatment; municipal solid waste; compost; біогаз; тверді побутові відходи; очищення стічних вод; переробка відходів; компост; кафедра електропостачання і енергоменеджменту